An Assessment of Entrepreneurship Development Constraints in Nigeria as Panacea for Ameliorating Unemployment. - Adamu, Alhaji Sule (2016)
Abstract The dynamic evolution of entrepreneurship universally accepted as a means of job creation, poverty alleviation, and promotion of economic prosperity leading to economic development has drawn interest among leaders, academicians and governments. It is in line with these enormous contributions that succeeding governments in Nigeria floated several programs and policies aimed at promoting entrepreneurship. Following identification of research gaps in literature review, this study explores Nigerian government funding intervention programs, its challenges and prospects of entrepreneurship development toward ameliorating unemployment in Nigeria. The study used an online questionnaire administered to Business forum of Nairaland for data collection. 113 active members participated in the survey out of a sample of 160 active online members. The research question and hypothesis raised were tested. Pearson Chi-Square test and descriptive statistics embedded in IBM SPSS version 22 were respectively used in testing the hypothesis and data analysis. The study revealed that government intervention programs were ineffective in ameliorating unemployment; while politicization of loans, nepotism, lack of co-operative group among unemployed graduates, early enterprise failure, failure by government in targeting the right people, lack of prosecution of corrupt government officials, inadequate orientation and enlightenment from government have constrained the realization of entrepreneurial development programs towards ameliorating unemployment in Nigeria. In the light of foregoing, the study offers useful recommendation in order to enhance entrepreneurship for employment generation. These are: entrenching of positive mindset by stakeholders in supporting entrepreneurship, reorganizing government entrepreneurial support agencies, auditing of policy programs for preventing replication and conflicts. In addition, conversion of confiscated farms from treasury looters into agricultural training centres, enlightenment programs on embracing self-employment, and creation of enabling environment for sustaining entrepreneurship in view of its critical contribution to developing Nigerian economy.